Effects of Sirrah-Bios PRRSV-RS vaccine on mortality rate and finisher pig performance - Potter, M. L.; Henry, Steven C.; Tokach, Lisa M.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,561 pigs (initially 4 d of age) were used to determine the effects of a porcine reproductive and respiratory syndrome virus (PRRSv) subunit vaccine, PRRSV-RS (Sirrah-Bios, Ames, IA), on mortality rate and finisher pig growth performance in a PRRSv-positive commercial herd. Pigs were randomly assigned by litter to either the subunit PRRSv vaccine or non-vaccinated control group. Pigs in the vaccinated group received an intramuscular injection of 1 mL PRRSV-RS vaccine at processing (approximately 4 d after birth) and again at weaning (approximately 24 d of age). Vaccinated and control pigs were comingled in a single nursery during the nursery phase. In the finishing phase, pigs were housed in a standard commercial curtain-sided finisher barn by treatment and gender by pen, with treatments randomly distributed across pens. Mortality was tracked from processing (4 d of age) to market (d 187 to 193). There was no difference between the control and vaccinated pigs for cumulative mortality (21.5% vs. 20.6%, P = 0.67) or for mortality during each production phase (processing to weaning: 9.5% vs. 7.1%, P = 0.08; nursery: 9.3% vs. 9.2%, P = 0.95; finishing: 4.4% vs. 5.9%, P = 0.20). Pigs were initially weighed by single-sex pens (control or vaccinated) 2 wk after placement into the finisher (d 0), and at that time, control and vaccinated mean pig weights were not different (58.4 vs. 58.7 lb, P = 0.90). Pens of pigs were subsequently weighed every 2 wk, and feed consumption was recorded to calculate ADG, ADFI, and F/G. Overall (d 0 to 112), control and vaccinated pig performance was similar (ADG: 1.96 vs. 1.93 lb, P = 0.45; ADFI: 5.35 vs. 5.36 lb, P = 0.94; F/G: 2.74 vs. 2.78, P = 0.15) throughout the finishing period. This resulted in no difference (P = 0.79) in off-test (d 112) weights between control (271.9 lb) and vaccinated (270.4 lb) pigs. These data indicate that this subunit PRRSv vaccine did not affect finisher pig performance or mortality in this commercial herd.
Keywords: Growth; Mortality; PRRSv; Vaccine; Swine